Low Hepatitis B vaccination rates among medical students in South Asia: A systematic review and meta-analysis. - Ramesh Lamichhane; Indra Dev Pathak; Bishnu Deep Pathak; Pritha Adhikari; Sagun Dawadi; Aashika Rai; Pratikshya Ojha; Kripa Maharjan; Kirtan Gautam; Nishan Dhakal; Madhusudan Saha (PLoS ONE)
Background and aims Current and future healthcare professionals, such as medical students, are at risk of contracting Hepatitis B virus infection. Vaccination against Hepatitis B is an effective means of prevention. However, studies have reported variable vaccination rates among medical students from different regions of South Asia. Understanding vaccination rates and barriers can guide effective interventions to protect future doctors. Therefore, we aimed to find out the vaccination rate among medical students in South Asia. Methods A comprehensive literature search was conducted across multiple databases (PubMed, PubMed Central, Scopus, Embase, CINAHL, Google Scholar, MEDLINE, and other sources) beginning from inception to July 15, 2024. Observational studies reporting vaccination rates among Bachelor of Medicine and Bachelor of Surgery (M.B.B.S.) students in South Asia were included. Two reviewers independently screened and performed the quality assessment. Pooled vaccination rates were calculated and visualized using a random-effects model in R Studio (Version 2023.12.0). Subgroup analysis was performed based on country and year of publication of the studies. Results Fifty studies from the South Asian region, including 12,231 participants, were included in the quantitative analysis. The overall pooled Hepatitis B vaccination rate using the random-effects model was 56% (CI: 49-63%), with significant heterogeneity among the included studies (I2 = 98%; P = 0). Subgroup analysis based on country revealed a significant regional variation in vaccination rate (59% in Pakistan, 57% in India, 55% in Nepal, and 41% in Bangladesh; P < 0.01). Lack of awareness, perceived low risk or necessity, concerns about side effects, logistical challenges, and lack of motivation have been reported as barriers to vaccination. Conclusion The overall vaccination rate was relatively low in South Asia, with significant regional variation. Based on the reported barriers, we recommend that relevant authorities focus on vaccination awareness, motivation, cost-effectiveness, logistics management, policy formulation, and monitoring.